Fire-resistant structural materials and methods for suppressing red heat

The fire-resistant structural material with a burnable coating layer addresses the challenge of red heat retention by ensuring the fireproof coating layer remains intact, enhancing fire resistance and preventing re-ignition.

JP7602382B2Active Publication Date: 2024-12-18SUMITOMO FORESTRY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021008933
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-22
Publication Date
2024-12-18
Estimated Expiration
2041-01-22

AI Technical Summary

Technical Problem

Existing fire-resistant structural materials, particularly those using square steel pipes, struggle to achieve one-hour fire resistance due to red heat remaining on the surface, which can lead to continued combustion and structural damage.

Method used

A fire-resistant structural material design incorporating a load support part made of wood or steel, a fireproof coating layer of solid wood, and a burnable coating layer that burns away upon exposure to flames, with a thickness of less than 25 mm, to prevent cracks and suppress red heat.

Benefits of technology

The design effectively suppresses red heat, preventing the fireproof coating layer from becoming red-hot and reducing the risk of re-ignition, while maintaining structural integrity during and after a fire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602382000001
    Figure 0007602382000001
  • Figure 0007602382000002
    Figure 0007602382000002
  • Figure 0007602382000003
    Figure 0007602382000003
Patent Text Reader

Abstract

To provide a fire resistant structure material and a red-heat suppression method that can prevent the fire resistant structure material from being red-heat.SOLUTION: A fire resistant structure material 1A comprises a wooden or steel load support part 11a, a fire resistant coating layer 12a that coats the load support part 11a and is made of pure wood, and a burnable coating layer 13a that coats the fire resistant coating layer 12a, is made of pure wood and has a thickness less than 25 mm, and when being exposed to flame, it is burned and destroyed by fire. When conducting a burning test for 60 minutes by using standard heating according to ISO834-1 on the fire resistant structure material 1A and a comparison structure material in which the burnable coating layer 13a of the fire resistant structure material 1A is replaced with the fire resistant coating layer 12a, it is preferable that a mass decreasing rate of the fire resistant structure material 1A is larger than that of the comparison structure material just after the end of heating, and a mass decreasing rate of the fire resistant structure material is smaller than that of the comparison structure material within 180 minutes after the end of heating.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a fire-resistant structural material and a method for suppressing glow. [Background technology]

[0002] Hybrid laminated timber is known as a fire-resistant structural material, and has been certified by the Minister of Land, Infrastructure, Transport and Tourism as a one-hour fire-resistant structural column by the Japan Laminated Timber Industry Cooperative. Hybrid laminated timber is constructed by covering a steel frame with pure wood laminated timber without using inorganic materials or chemical impregnation. H-shaped steel is used for the steel frame. The wood species that make up the laminated timber are larch or Douglas fir. Hybrid laminated timber achieves one-hour fire resistance by taking advantage of the thermal conductivity of H-shaped steel and the heat absorption due to the effect of heat capacity to improve the fire-stopping effect of the wood.

[0003] Also, various techniques have been proposed for obtaining fire-resistant members by providing a burn margin on the surface of wood or a composite material of wood and other materials, for example, Patent Document 1 proposes a structural material that includes a load-bearing layer and a burn margin layer that is arranged on the outside of the load-bearing layer and is made of wood with a lower thermal inertia than the load-bearing layer, while Patent Document 2 proposes a structural material that includes a load-bearing layer, a fire-retardant layer that is arranged on the outside of the load-bearing layer and has a heat insulating material, and a burn margin layer that is arranged on the outside of the fire-retardant layer and is made of wood with a predetermined thickness. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-36457 A [Patent Document 2] JP 2005-48585 A Summary of the Invention [Problem to be solved by the invention]

[0005] In general, it is difficult to stably achieve one-hour fire resistance in pure wood laminated lumber. Specifically, when the laminated lumber is left to cool after heating, red heat may remain on the surface of the pure wood laminated lumber, and the burning may continue. In the hybrid laminated lumber, the larch or Douglas fir that constitutes the laminated lumber is a species that is easy to stop burning, and the temperature rise of the wood covering the H-shaped steel is suppressed by the H-shaped steel, so that it is considered that the one-hour fire resistance is realized. In addition, the shape of the H-shaped steel is also considered to contribute to the one-hour fire resistance. Specifically, in the hybrid laminated lumber, the web part of the H-shaped steel is located in the center of the cross section of the laminated lumber, and the flange part of the H-shaped steel is located on the outer periphery of the cross section, so that heat flows from the flange part to the web part, and heat flows from the outer periphery to the inside where the temperature rise is gradual, and it is considered that the fire resistance is further improved.

[0006] On the other hand, when square steel pipes are used as the steel frame of hybrid laminated timber, the shape of the square steel pipes makes it easy for the temperature to rise across their entire surface, so the thermal capacity effect cannot be utilized as much as with H-shaped steel, and one-hour fire resistance cannot be achieved. In Patent Documents 1 and 2, there is no consideration whatsoever about achieving one-hour fire resistance when square steel pipes are used, and there is room for improvement in fire resistance.

[0007] The present inventors have thoroughly investigated the reason why red heat remains in the above-mentioned pure wood laminated lumber, and have found that, after the surface of the pure wood laminated lumber burns and a charred layer is formed, cracks may occur in the charred layer or parts of the charred layer may be missing, forming unevenness on the surface of the charred layer, and in such cases, red heat remains inside the charred layer, such as in the cracks that have occurred in the charred layer, and combustion continues.

[0008] An object of the present invention is to provide a fire-resistant structural material and a method for suppressing red heat, which are capable of suppressing red heat of the fire-resistant structural material. [Means for solving the problem]

[0009] The present invention provides a fire-resistant structural material comprising: a load-bearing section made of wood or steel; a fire-resistant coating layer made of solid wood that covers the load-bearing section; and a burn-dissipating coating layer made of solid wood and having a thickness of less than 25 mm that covers the fire-resistant coating layer and that burns and dissipates when exposed to flames.

[0010] The present invention also provides a method for suppressing red-heating, in which a structural material having a wooden or steel load-bearing part and a fire-resistant coating layer made of pure wood covering the load-bearing part is covered with a burn-resistant coating layer made of pure wood that burns and is destroyed when exposed to flames, thereby preventing cracks from occurring on the surface of the fire-resistant coating layer and suppressing the fire-resistant coating layer from red-heating, wherein the thickness of the burn-resistant coating layer is less than 25 mm. Effect of the Invention

[0011] According to the present invention, it is possible to provide a fire-resistant structural material and a method for suppressing red heat, which can suppress the fire-resistant structural material from red heat. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a cross-sectional view showing a fire-resistant structural material according to a preferred embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing positions at which temperature changes were measured when a combustion test was carried out on the fire-resistant structural material of Example 1. As shown in FIG. [Diagram 3] FIG. 3 is a diagram showing the positions at which temperature changes were measured when a combustion test was carried out on the fire-resistant structural material of Example 2. [Figure 4] FIG. 4 is a diagram showing the positions at which temperature changes were measured when a combustion test was carried out on the fire-resistant structural material of Comparative Example 1. As shown in FIG. [Diagram 5] 5(a) to (c) are graphs showing the results of measuring the temperature of the fire-resistant structural material of Example 1 when a combustion test was performed on the fire-resistant structural material. [Figure 6] 6(a) to (d) are graphs showing the results of measuring the temperature of the fire-resistant structural material of Example 2 when a combustion test was performed on the fire-resistant structural material. [Figure 7] 7(a) to (c) are graphs showing the results of measuring the temperature of the fire-resistant structural material of Comparative Example 1 when a combustion test was performed on the fire-resistant structural material. [Figure 8] FIG. 8 is a photograph showing the state of the fire-resistant structural material of Example 1 after the combustion test. [Figure 9] FIG. 9 is a photograph showing the state of the fire-resistant structural material of Example 2 after the combustion test. [Figure 10] FIG. 10 is a photograph showing the state of the fire-resistant structural material of Comparative Example 1 after the combustion test. [Figure 11] FIG. 11 is a graph showing the results of carrying out a combustion test for Example 3 and Comparative Example 2 and measuring the mass of the fire-resistant structural materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will now be described in detail based on preferred embodiments thereof. A fireproof structural material 1A, which is a preferred embodiment of the fireproof structural material of the present invention, is shown in Fig. 1. Fig. 1 shows a schematic cross section perpendicular to the axial direction of the fireproof structural material 1A. The fireproof structural material 1A of this embodiment is a structural square timber used as a beam or pillar of a building. As shown in Fig. 1, the fireproof structural material 1A includes a load-bearing portion 11a made of wood or steel, a fireproof coating layer 12a, and a burn-off coating layer 13a.

[0014] The cross-sectional design of the load-supporting portion 11a is such that the load-supporting portion 11a alone is structurally safe against long-term loads such as fixed loads, live loads, and snow loads. Such cross-sectional designs are well known. The cross-sectional shape of the load-supporting portion 11a is rectangular, and the vertical and horizontal lengths of the load-supporting portion 11a in the cross-section of the fire-resistant structural material 1A can be appropriately changed depending on the shape or size of the beams or columns.

[0015] The fire-resistant coating layer 12a covers the load-supporting portion 11a. In this embodiment, the fire-resistant coating layer 12a covers four axial side surfaces of the load-supporting portion 11a. When the fire-resistant structural material 1A is a beam, the fire-resistant coating layer 12a may cover three axial side surfaces of the load-supporting portion 11a. The side of the fire-resistant structural material 1A on which the fire-resistant coating layer 12a is not formed may be covered by placing a floor or the like thereon to cover the upper side of the load-supporting portion 11a.

[0016] The burnable coating layer 13a coats the fire-resistant coating layer 12a. The burnable coating layer 13a is adapted to burn and be burned when exposed to a flame. The thickness of the burnable coating layer 13a is less than 25 mm. Since the thickness of the burnable coating layer 13a is less than 25 mm, the burnable coating layer 13a is adapted to be burned reliably. Since the burnable coating layer 13a has such a configuration, the fire-resistant structural material 1A of this embodiment can prevent the fire-resistant coating layer 12a from becoming red-hot. The reason why the fire-resistant structural material 1A of this embodiment can prevent the fire-resistant coating layer 12a from becoming red-hot is not completely clear, but the inventors speculate as follows.

[0017] The combustion of the fire-resistant structural material 1A is thought to proceed in the following order. When the fire-resistant structural material 1A is exposed to a flame, first, a pyrolysis reaction mainly occurs in the burn-resistant coating layer 13a, and the burn-resistant coating layer 13a is carbonized (first stage). In the first stage, the temperature of the fire-resistant coating layer 12a rises. Then, the pyrolysis reaction of the burn-resistant coating layer 13a ends, and an oxidation reaction of the burn-resistant coating layer 13a mainly occurs, and the burn-resistant coating layer 13a turns to ash and begins to burn (second stage). In the second stage, a pyrolysis reaction mainly occurs in the fire-resistant coating layer 12a, and the fire-resistant coating layer 12a is carbonized. Then, the burn-resistant coating layer 13a is completely burned (third stage). In the fourth stage, an oxidation reaction occurs together with a pyrolysis reaction in the fire-resistant coating layer 12a. Then, the pyrolysis reaction of the fire-resistant coating layer 12a ends, and an oxidation reaction of the fire-resistant coating layer 12a mainly occurs (fourth stage). Thereafter, the oxidation reaction of the fire-resistant coating layer 12a ends, and the fire-resistant structural material 1A stops burning (fifth stage). In this way, in the fireproof structural material 1A of this embodiment, the pyrolysis reaction of the fireproof coating layer 12a occurs some time after the start of combustion. Therefore, the surface of the fireproof coating layer 12a can be kept smooth for some time after the start of combustion. In addition, the time during which the fireproof structural material 1A is burning during which the pyrolysis reaction or oxidation reaction of the fireproof coating layer 12a is occurring can be shortened. Due to these factors, the fireproof structural material 1A of this embodiment is less likely to develop cracks or the like in the fireproof coating layer 12a, and it is possible to prevent it from continuing to glow red.

[0018] In addition, even if cracks or the like are generated in the burn-resistant coating layer 13a due to a pyrolysis reaction or an oxidation reaction, and red heat is generated in the cracks, the burn-resistant coating layer 13a is burned away, so the burn-resistant coating layer 13a does not continue to be red-heated. Therefore, the red heat of the burn-resistant coating layer 13a can be prevented from being transmitted to the fire-resistant coating layer 12a. This also contributes to suppressing the red heat of the fire-resistant coating layer 12a.

[0019] The thickness of the burnable coating layer 13a is preferably less than 25 mm, more preferably less than 20 mm, from the viewpoint of making the burnable coating layer 13a more likely to burn when the fire-resistant structural material 1A burns. Here, if the thickness is 25 mm or more, it is not preferable because the burning time until the layer is burned increases, and the member itself continues to burn for a long time. Moreover, the thickness of the burnable coating layer 13a is preferably 10 mm or more, more preferably 15 mm or more, from the viewpoint of delaying the start of the thermal decomposition reaction or oxidation reaction of the fire-resistant coating layer 12a.

[0020] It is preferable that the fire-resistant structural material 1A of this embodiment satisfies the following criteria (1) and (2) when a 60-minute combustion test using standard heating in accordance with ISO834-1 is conducted on the fire-resistant structural material 1A and a comparative structural material in which the burn-away coating layer 13a of the fire-resistant structural material 1A is replaced with a fire-resistant coating layer 12a. Criterion (1): Immediately after heating was completed, the fire-resistant structural material 1A had a greater rate of mass reduction than the comparative structural material. Criterion (2): Within 180 minutes after the end of heating, the mass loss rate of Fire-Resistant Structural Material 1A is smaller than that of the Comparative Structural Material. The fact that the fire-resistant structural material 1A satisfies the criterion (1) is considered to mean that the burn-resistant coating layer 13a is more likely to burn when exposed to a flame. Also, the fact that the fire-resistant structural material 1A satisfies the criterion (2) is considered to mean that the thermal decomposition reaction and oxidation reaction of the fire-resistant coating layer 12a settle at an earlier stage after the burn-resistant coating layer 13a is burned. Therefore, the fire-resistant structural material 1A that satisfies the criteria (1) and (2) can further suppress the red heat of the fire-resistant coating layer 12a.

[0021] To describe the comparative structural material in detail, the comparative structural material has the same structure as the fire-resistant structural material 1A, except that the burn-resistant coating layer 13a in the fire-resistant structural material 1A is replaced with a fire-resistant coating layer 12a. The cross-sectional dimensions of the comparative structural material are the same as those of the fire-resistant structural material 1A. The comparative structural material can also be manufactured by using a fire-resistant coating layer 12a having the same thickness as the combined thickness of the burn-resistant coating layer 13a and the fire-resistant coating layer 12a in place of the burn-resistant coating layer 13a and the fire-resistant coating layer 12a in the fire-resistant structural material 1A.

[0022] The mass loss rate can be measured, for example, as follows. <Method for measuring mass loss rate> First, a 60-minute combustion test is conducted for the fire-resistant structural material 1A and the comparative structural material using standard heating in accordance with ISO 834-1. During the test, the mass change of the fire-resistant structural material is measured. The mass of the structural material at T minutes after the start of heating is W, and the mass of the structural material at T minutes after the start of heating is T Δ The mass of the structural material in W Δ Then, the mass loss rate is calculated using the following formula. Mass reduction rate (kg / min)=(WW Δ ) / (T Δ -T) When calculating the mass loss rate immediately after the end of heating, T should be set to 60 (min).

[0023] The thickness of the fire-resistant coating layer 12a is preferably 60 mm or more, more preferably 75 mm or more, from the viewpoint of making the fire-resistant coating layer 12a more likely to remain when the fire-resistant structural material 1A burns and improving the fire resistance of the fire-resistant structural material 1A. When the load-supporting portion 11a is made of steel, the thickness of the fire-resistant coating layer 12a is preferably 90 mm or less, more preferably 75 mm or less, from the viewpoint of taking advantage of the thermal conductivity and the heat absorption due to the influence of the heat capacity to improve the fire-stopping effect of wood.

[0024] Next, the constituent materials of the fire-resistant structural material 1A will be described. As described above, the load-supporting portion 11a is made of wood or steel. When the load-supporting portion 11a is made of wood, materials such as laminated timber, lumber, cross-laminated timber (CLT), laminated veneer lumber (LVL), and parallel strand lumber (PSL) can be used as the load-supporting portion 11a. When the load-supporting portion 11a is made of wood, the load-supporting portion 11a may be a laminate in which a plurality of laminas are laminated and bonded in a direction perpendicular to one direction, and the laminate is arranged in the same direction to have a rectangular cross-sectional shape. When the load supporting portion 11a is made of steel, it is possible to use a square steel pipe, an H-shaped steel, a square steel, a flat steel, a channel steel, etc. Also, even if it has a shape other than these, it can be used as the load supporting portion 11a as long as it can be surrounded by the fire-resistant coating layer 12a.

[0025] The fire-resistant coating layer 12a and the burn-off coating layer 13a are made of a wood material such as pure wood. In this specification, pure wood means wood that does not contain any flame retardant, non-combustible material, inorganic material, etc.

[0026] Examples of the pure wood forming the fire-resistant coating layer 12a include laminated timber, lumber, cross-laminated timber (CLT), laminated veneer lumber (LVL), parallel strand lumber (PSL), and plywood. CLT and laminated timber may be laminated in the short direction with a plurality of laminas having a rectangular cross section, with the vertices of the rectangles overlapping. Examples of the pure wood forming the fire-resistant coating layer 12a include larch, Douglas fir, red pine, Yezo spruce, white birch, cypress, Japanese cedar, zelkova, Scots pine, and radiata pine, with larch being preferred among these.

[0027] The pure wood constituting the burn-resistant coating layer 13a may be, for example, laminated timber, lumber, cross-laminated timber (CLT), laminated veneer lumber (LVL), parallel strand lumber (PSL), and plywood. CLT and laminated timber may be made by stacking a plurality of laminas having rectangular cross sections in the short direction, with the vertices of the rectangles overlapping. The pure wood species constituting the burn-resistant coating layer 13a may be, for example, cedar, fir, SPF, and balsa, with cedar being preferred among these.

[0028] The bonding between the load-bearing portion 11a and the fire-resistant coating layer 12a, the bonding between the fire-resistant coating layer 12a and the burn-off coating layer 13a, and the bonding between the lamina constituting each of the load-bearing portion 11a, the fire-resistant coating layer 12a, and the burn-off coating layer 13a can be performed using various known adhesives that have been conventionally used in the manufacture of fire-resistant structural materials, such as resorcinol resin-based adhesives, resorcinol-phenol-based resin adhesives, aqueous polymeric isocyanate resin-based adhesives, polyurethane-based adhesives, and vinyl acetate-based adhesives. Of these, resorcinol-phenol-based resin adhesives are preferred from the viewpoint of further suppressing red heat.

[0029] Next, the glow-in suppression method of the present invention will be described. A preferred embodiment of the glow-in suppression method of the present invention is a method of covering a structural material having a load-supporting portion 11a and a fire-resistant coating layer 12a that covers the load-supporting portion 11a with a burnable coating layer 13a. According to the glow-in suppression method of this embodiment, the above-mentioned fire-resistant structural material 1A is preferably obtained. According to the glow-in suppression method of this embodiment, cracks are prevented from occurring on the surface of the fire-resistant coating layer 12a, and the glow-in suppression of the fire-resistant coating layer 12a can be suppressed.

[0030] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to such examples. EXAMPLES

[0031] Example 1 A fire-resistant structural material having the same structure as the fire-resistant structural material 1A shown in FIG. 1 was manufactured. Specifically, a fire-resistant structural material having a wooden load-bearing portion was manufactured. The fire-resistant structural material has a cross-sectional dimension of 360 mm×360 mm and an axial length of 3500 mm. The cross-sectional dimension of the load-bearing portion is 180 mm×180 mm, the thickness of the fire-resistant coating layer is 75 mm, and the thickness of the combustible coating layer is 15 mm. The load-bearing part and the fire-resistant coating layer are made of larch (density: 0.50 g / cm 3 The composite wood used was cedar (density: 0.40 g / cm3, moisture content: 12.3%). 3 The adhesive used in the manufacture of the fire-resistant structural materials was a resorcinol-phenolic resin adhesive.

[0032] Example 2 A fireproof structural material having the same configuration as the fireproof structural material 1A shown in FIG. 1 was manufactured. Specifically, a fireproof structural material having a square steel pipe as a load supporting part was manufactured. The fireproof structural material has a cross-sectional dimension of 385 mm x 385 mm and an axial length of 3300 mm. The square steel pipe as the load supporting part has a cross-sectional dimension of 200 mm x 200 mm and a thickness of 9 mm. The fireproof coating layer has a thickness of 75 mm, and the combustible coating layer has a thickness of 15 mm. In Example 2, a spacer having a thickness of 2.5 mm was placed between the load supporting part and the fireproof coating layer. The spacer was placed on each of the four side surfaces along the axial direction of the load supporting part. The square steel pipes used were STKR400 as specified in JIS G 3466. The spacers were made of cedar plywood. The fireproof coating layer was made of larch (density: 0.49 g / cm 3 The laminated wood used was cedar (density: 0.36 g / cm3, moisture content: 12.2%). 3 The laminated wood used was 10.0% moisture content.

[0033] Comparative Example 1 A fireproof structural material was manufactured in the same manner as in Example 1, except for the following points: The thickness of the fireproof coating layer was 90 mm, and no burn-off coating layer was provided. The density of larch was 0.53 g / cm 3 The adhesive used was a ferroresorcinol co-condensation resin (PRF) based adhesive.

[0034] (evaluation) (Combustion test) The fireproof structural materials of Examples 1 and 2 and Comparative Example 1 were placed in a test furnace in an upright state, and each of the four sides was heated for one hour by standard heating according to ISO834-1, which assumes a normal fire. After the heating was completed, Example 1 and Comparative Example 1 were allowed to cool in the furnace for 8 hours, and Example 2 was allowed to cool for 11 hours. At that time, the temperature change was measured at each position indicated by black dots in Figures 2 to 4, and the temperature change over time at each position was recorded. Hereinafter, each position indicated by black dots in Figures 2 to 4 will be described as position 1, position 2, etc., using the numbers shown in Figures 2 to 4. The results of measuring the temperature change at each position are shown in Figures 5 to 7, respectively. In addition, the state of the heating surface of Examples 1 and 2 and Comparative Example 1 was visually confirmed. The state of the fireproof structural materials of Examples 1 and 2 and Comparative Example 1 after the combustion test is shown in Figures 8 to 10, respectively.

[0035] In Example 1, as shown in FIGS. 5(a) to (c), at all positions where the temperature change was measured, after the temperature dropped, the temperature did not rise again until the end of the test. In addition, in the fire-resistant structural material of Example 1, the cedar boards on the surface continued to burn for a while immediately after the end of heating, but the flaming combustion did not significantly affect the temperature inside the furnace. It was also observed that the temperature inside the furnace also dropped as the flames died down. In addition, the cedar boards that did not burn out during heating continued to burn red hot while attached to the surface layer of the larch, but it was confirmed that they burned out and turned to ash as their volume decreased and they were carbonized, or that they fell off in the form of small charcoal and ash. In addition, since the cedar and the larch were secondary bonded with a resorcinol-based resin adhesive, the cedar did not fall off easily. Red-hot cedar sometimes fell onto the hearth, but the fallen cedar did not burn for a long time. After the cedar burned out, the carbonized layer of the larch gradually became exposed. In Example 1, the surface layer of the carbonized larch was not deeply carbonized and solidly carbonized compared to Comparative Example 1, but was in a relatively shallow carbonized state, and it was observed that the red-hot parts of the surface layer were crumbling away in small pieces.

[0036] In Example 2, as shown in FIGS. 6(a) to (d), at all positions where the temperature change was measured, after the temperature dropped, it did not rise again until the end of the test. In addition, the furnace temperature and the internal temperature of the fire-resistant structural material of Example 2 had both started to decrease sufficiently 12 hours after the start of the combustion test. No large cracks or the like were formed on the surface layer of the fire-resistant structural material of Example 2. Although the surface layer was slightly red-hot when the structural material was removed from the furnace, it was not hot enough to reignite and was burned out after a few hours.

[0037] In Comparative Example 1, as shown in FIG. 7(a), at position 5, the temperature did not decrease from the end of heating to the end of the test, and combustion continued. At positions 3 and 7, the temperature reached a peak, then decreased, and then increased again. From this, it is believed that after the flames had gone out at positions 3 and 7, the red heat remaining in other positions was transferred to positions 3 and 7, and combustion resumed. At positions 12, 13, and 14, the temperature also decreased and then increased, as shown in FIG. 7(b), so it is believed that the red heat remaining in other positions was transferred, and combustion resumed.

[0038] In addition, the fireproof structural material of Comparative Example 1 had large cracks on the surface after heating began. Also, many charred layers were observed falling off during heating and in the early stages of cooling. Even after heating ended, strong red-hot combustion continued inside the cracks (uneven parts) that had occurred throughout the component, and major damage was observed in the fireproof coating layer. In Comparative Example 1, the charred layer of the larch remained relatively solid, and the cracks were deep. From the results of Examples 1 and 2 and Comparative Example 1, it is apparent that the present invention can suppress the red heat of a fire-resistant structural material.

[0039] In Example 2, as shown in Figure 6(b), the temperature at position 10 located at a corner of the fire-resistant structural material peaks and then starts to decline, and the temperature at position 6 located in the portion between the corners of the fire-resistant structural material (hereinafter referred to as the "center") also peaks and then starts to decline. In contrast, in Example 1, as shown in Figure 5(b), the temperature change at position 6 located in the center of the fire-resistant structural material does not follow the temperature change at position 9 located at the corner of the fire-resistant structural material. This difference is thought to be due to the difference in the load-supporting parts of Examples 1 and 2. Specifically, in Example 2, since the fire-resistant structural material has a square steel pipe as a load-supporting part, it is considered that heat in the vicinity of the corner of the structural material, more specifically, at a position where the surface of the corner of the square steel pipe facing the fire-resistant coating layer (hereinafter referred to as the outer surface of the corner of the square steel pipe) and the surface of the fire-resistant coating layer facing the square steel pipe (hereinafter referred to as the inner surface of the fire-resistant coating layer) are approximately parallel, is transferred to the center of the structural material via the square steel pipe, which has a high thermal conductivity. The outer surface of the corner of the square steel pipe and the inner surface of the fire-resistant coating layer being approximately parallel means that the curvature of the outer surface of the corner of the square steel pipe in a direction parallel to the inner surface of the fire-resistant coating layer is approximately 0. According to Example 2, it is possible to suppress the concentration of heat in the vicinity of the corner of the fire-resistant structural material, and it is considered that red heat can be further suppressed.

[0040] Example 3 A fire-resistant structural material having the same structure as the fire-resistant structural material 1A shown in FIG. 1 was manufactured. Specifically, a fire-resistant structural material having a wooden load-bearing portion was manufactured. The fire-resistant structural material has a cross-sectional dimension of 330 mm x 330 mm and an axial length of 1600 mm. The cross-sectional dimension of the load-bearing portion is 180 mm x 180 mm, the thickness of the fire-resistant coating layer is 60 mm, and the thickness of the combustible coating layer is 15 mm. The load-bearing part and the fire-resistant coating layer are made of larch (density: 0.49 g / cm 3 The laminated wood used was cedar (density: 0.33 g / cm3, moisture content: 9.5%). 3 The laminated wood used was 10.9% moisture content.

[0041] Comparative Example 2 A fireproof structural material was manufactured in the same manner as in Example 3, except for the following points: The thickness of the fireproof coating layer was 75 mm, and no burn-off coating layer was provided. The density of the larch was 0.50 g / cm 3 The moisture content was 9.7%.

[0042] (Evaluation of mass loss rate) The fireproof structural materials of Example 3 and Comparative Example 2 were hung from the ceiling of a test furnace so that the axial direction of the fireproof structural materials was aligned with the vertical direction, and each of the four sides was heated for one hour by standard heating according to ISO834-1, which assumes a normal fire. After the heating was completed, the materials were left to cool in the furnace for six hours. At that time, the mass change of each fireproof structural material was measured, and the change in mass of each structural material over time was recorded. The results are shown in FIG. 11. Note that, from the start of heating until 30 minutes, the output of the heating burner was increased to increase the temperature inside the furnace, so the pressure inside the furnace was prone to fluctuating, making it difficult to accurately measure the mass. Therefore, FIG. 11 shows the measurement results after 30 minutes when the pressure inside the furnace stabilized.

[0043] As shown in FIG. 11, immediately after the end of heating, that is, 60 minutes after the start of heating, Example 3 has a higher mass reduction rate than Comparative Example 2. Also, within 180 minutes after the end of heating, specifically, 30 minutes after the end of heating, Example 3 has a lower mass reduction rate than Comparative Example 2. Immediately after the end of heating, Example 3 has a higher rate of change in mass reduction rate than Comparative Example 2, but thereafter, Example 3 has a lower rate of change in mass reduction rate than Comparative Example 2. Also, when comparing the fireproof structural material of Example 3 and the fireproof structural material of Comparative Example 2 after the combustion test, the fireproof structural material of Example 3 had no large cracks or cracks and no red heat remained, whereas the fireproof structural material of Comparative Example 3 had large cracks or cracks and red heat remained. Therefore, it can be seen that the fireproof structural material of Example 3 can suppress red heat. [Explanation of symbols]

[0044] 1A Fireproof structural material 11a Load support part 12a Fireproof coating layer 13a Burnable coating layer

Claims

1. A fire-resistant structural material having one-hour fire resistance, A load-bearing section made of wood or steel; A fire-resistant coating layer made of solid wood that covers the load-bearing portion; a burnable coating layer made of pure wood having a thickness of 10 mm or more and less than 20 mm, which covers the fire-resistant coating layer and burns when exposed to a flame; A fire-resistant structural material, in which the pure wood constituting the fire-resistant coating layer and the pure wood constituting the burn-resistant coating layer are joined at the boundary between the fire-resistant coating layer and the burn-resistant coating layer.

2. The wood species constituting the fire-resistant coating layer is larch, 2. The fire-resistant structural material according to claim 1, wherein the wood species constituting the burn-off coating layer is Japanese cedar.

3. 3. The fire-resistant structural material according to claim 1, wherein the load-bearing portion is a square steel pipe.

4. A structural material having a load-bearing part made of wood or steel and a fire-resistant coating layer made of solid wood that covers the load-bearing part is covered with a burnable coating layer made of solid wood that burns and burns up when exposed to flames, A method for suppressing red heat by preventing cracks from occurring on the surface of the fire-resistant coating layer and suppressing red heat of the fire-resistant coating layer, The structural material covered with the burn-resistant coating layer has a one-hour fire resistance, and at the boundary between the fire-resistant coating layer and the burn-resistant coating layer, the pure wood constituting the fire-resistant coating layer and the pure wood constituting the burn-resistant coating layer are joined together, The heat suppression method, wherein the thickness of the burnable coating layer is 10 mm or more and less than 20 mm.

Citation Information

Patent Citations

  • 22system structure system

    JP1979005349A

  • Structural material and building

    JP2005036457A

  • Structure, and building

    JP2005048585A

  • Joint structure with between woody structure material and wall

    JP2015040431A

  • Woody structure member

    JP2018091108A